The book of Lord Shang : apologetics of state power in early China - Shang, Yang, -338 B.C (Translations from the Asian classics., 2017)
Compiled in China in the fourth-third centuries B.C.E., The Book of Lord Shang argues for a new powerful government to penetrate society and turn every man into a diligent tiller and valiant soldier. Creating a "rich state and a strong army" will be the first step toward unification of "All-under-Heaven." These ideas served the state of Qin that eventually created the first imperial polity on Chinese soil. In this new translation, The Book of Lord Shang's intellectual boldness and surprisingly modern-looking ideas shine through, underscoring the text's vibrant contribution to global political